2023
DOI: 10.3389/fnut.2023.1099880
|View full text |Cite
|
Sign up to set email alerts
|

Corchorus olitorius extract exhibit anti-hyperglycemic and anti-inflammatory properties in rodent models of obesity and diabetes mellitus

Abstract: Obesity and type 2 diabetes (T2D) are chronic conditions with detrimental impacts on the overall health of individuals. Presently, the use of pharmacological agents in obesity and T2D offers limited benefits and pose side effects. This warrant studies on remedies that are less toxic and inexpensive while effective in ameliorating secondary complications in obesity and T2D. Plant-based remedies have been explored increasingly due to their remarkable properties and safety profile. We searched for pre-clinical ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…In South Africa, traditional medicine has existed for a long time, with practitioners providing care to the public, although some of these medicinal plants are not properly verified by botanists for use in diabetes [11]. More recently, Mokgalaboni et al [12] reported a significant effect of Corchorus olitorius in animal models of diabetes on hyperglycemia, oxidative stress, and inflammation. Although the results showed potential benefits The literature suggests that any therapeutic approach that can ameliorate oxidative stress may help control T2D and associated CVD.…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, traditional medicine has existed for a long time, with practitioners providing care to the public, although some of these medicinal plants are not properly verified by botanists for use in diabetes [11]. More recently, Mokgalaboni et al [12] reported a significant effect of Corchorus olitorius in animal models of diabetes on hyperglycemia, oxidative stress, and inflammation. Although the results showed potential benefits The literature suggests that any therapeutic approach that can ameliorate oxidative stress may help control T2D and associated CVD.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, our team recently found the potential beneficial effects of Corchorus olitorius and curcumin in a rodent model of obesity and DM and T2DM, respectively [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%